Measurements of gamma-ray emission probabilities of 241, 243Am and 239Np. Issue 11 (1st November 2016) - Terada, Kazushi; Nakamura, Shoji; Nakao, Taro; Kimura, Atsushi; Iwamoto, Osamu; Harada, Hideo; Takamiya, Koichi; Hori, Jun-ichi
ABSTRACT: Gamma-ray emission probabilities of 241, 243 Am and 239 Np have been precisely measured with gamma- and alpha-ray spectroscopic methods. The activities of the samples were determined by measuring alpha particles using a Si semiconductor detector. Gamma rays emitted from the samples were measured with a planar type High-Purity Germanium (HPGe) detector. An efficiency curve of the HPGe detector was derived with uncertainties from 0.7% to 2.5% by combining measured efficiencies and Monte Carlo simulation. The gamma-ray emission probabilities for the major gamma rays of these nuclides were determined with uncertainties less than 1.2%.